2016
DOI: 10.1021/acs.jafc.6b01086
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Food Allergic Activity of Sulfated Polysaccharide from Gracilaria lemaneiformis is Dependent on Immunosuppression and Inhibition of p38 MAPK

Abstract: (2016) AntiFood allergic activity of sulfated polysaccharide from Gracilaria lemaneiformisis dependent in immunosuppression and inhibition of p38 MAPK. Journal of Agricultural and Food Chemistry, 64 (22). pp. 4536-4544. ISSN 0021-8561Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/43933/1/Revised%20Manuscript1.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 42 publications
1
66
0
Order By: Relevance
“…32) Furthermore, natural polysaccha- rides from marine algae (Gracilaria lemaneiformis) 33) and terrestrial plants (Ganoderma tsugae and Angelica sinensis) 34,35) have been shown to exhibit inhibitory effects against immunoglobulin E (IgE)-mediated mast cell degranulation accompanied by the release of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…32) Furthermore, natural polysaccha- rides from marine algae (Gracilaria lemaneiformis) 33) and terrestrial plants (Ganoderma tsugae and Angelica sinensis) 34,35) have been shown to exhibit inhibitory effects against immunoglobulin E (IgE)-mediated mast cell degranulation accompanied by the release of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…ESP and GSP and their corresponding depolymerized products exhibited absorption peaks at 3438, 2935, and 1064 cm −1 , which are characteristic absorptions of -OH, C-H, and C-O, respectively [15]. The peak at 933 cm −1 can be attributed to 3,6-AG (C-O-S) [16]. The most important peaks for ESP and GSP and their depolymerized products are located at approximately 1244 and 1265 cm −1 , respectively, which correspond to the stretching vibration of the ester sulfate groups (S=O) [6,17].…”
Section: Effect Of Depolymerization On the Antibacterial Activity Of mentioning
confidence: 97%
“…11 Moreover, a sulfated polysaccharide isolated from Gracilaria lemaneiformis showed signicantly higher MW (152.5 kDa) and galactose content (87.49%), but lower sulfate content (11.26%), compared to our results. 12 These differences might be due to various factors, including the different extraction methods and/or different geographical origins of the materials used in the experiment.…”
Section: Characteristics Of the Polysaccharides From Gracilaria Lemanmentioning
confidence: 99%
“…11 Further, polysaccharides from Gracilaria lemaneiformis (GLP) have been found to possess various biological activities such as antioxidant, antimutagenic, anti-food allergic, antitumor and hypoglycemic effects. [10][11][12] However, the effect of GLP on diabetes induced by streptozotocin (STZ) (a naturally occurring chemical to induce toxicity in the insulin-producing pancreatic b cells of mammals), have not been investigated and the underlying mechanisms remained unknown. Further, polysaccharides with good water solubility and relatively low molecular weight (MW) likely possess greater bioactivities.…”
Section: Introductionmentioning
confidence: 99%